Leadership Styles of Female Principals at SMK Negeri 1 Penawar Tama and SMK Negeri 1 Banjar Margo Tulang Bawang Lampung - Ari Setioko; Meiliana Bustari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
School leadership plays a strategic role in improving educational quality through effective management, the creation of a positive school culture, and the achievement of learning outcomes, while women’s participation in educational leadership continues to face structural and cultural challenges related to gender stereotypes. This study aims to analyze the leadership styles of female principals at SMK Negeri 1 Penawar Tama and SMK Negeri 1 Banjar Margo, identify supporting and inhibiting factors, and examine the strategies implemented to improve school quality. The research employed a descriptive qualitative approach, with principals, teachers, and students as research subjects. Data were collected through in-depth interviews, passive participatory observation, and documentation, and were analyzed using interactive qualitative analysis techniques involving data condensation, data display, and conclusion drawing, with validity ensured through triangulation and member checks. The results indicate that female principals apply a combination of democratic-participatory, transformational, visionary, humanistic-communicative, and professional exemplary leadership styles. These leadership practices are reflected in inclusive decision-making, open communication, moral exemplarity, and strategic programs oriented toward student competence and institutional development. Supporting factors include strong personal commitment, high discipline, a conducive school climate, and stakeholder support, while inhibiting factors consist of limited infrastructure, policy changes, internal differences of opinion, and gender-based social pressures. The study concludes that, despite existing obstacles, female principals are able to implement adaptive and participatory leadership strategies that foster a positive work climate, enhance school community involvement, and contribute significantly to improving the quality and sustainability of vocational education.